PEMBUATAN BAHAN BAKAR PADAT DARI PELEPAH SAWIT DENGAN TAPIOKA SEBAGAI FILLER MELALUI PROSES DENSIFIKASI - Nasution, Muhammad Hatta; Helwani, Zuchra; Komalasari, Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Palm frond only used as a source of raw materials for animal feed, compost and organic fertilizer in the plantation. Palm frond has a calorific value of 15,18 MJ/kg with a density of 0.138 g/cm3. The calorific value can be increased by densification. Densification is one method to increase the density of the biomass so that it will increase the calorific value of the biomass. The purpose of this research is to produce solid fuel products from palm fronds uses densification process, to determine the characteristics of the product and determine the effect of tapioca filler composition and pressure at densification for density, calorific value and proximate. The composition of tapioca filler used were 5, 10 15 and 20%. Pressure used were 50, 75 and 100 bar. The particle size used were less than 20 mesh. The highest density of the product is 0.858 gr/cm3 was obtained at tapioca filler composition 20% and pressure 100 bar. The highest calorific value of the product is 16,16 MJ/kg was obtained at tapioca filler composition 15% filler and pressure 75 bar. Variations of filler composition and pressure give a significant effect the density of the product.Keywords : Densification, Density, Filler, Pressure, Palm Fronds.